Positive and negative solutions for a class of Kirchhoff type problems on unbounded domain. (February 2015) - Fan, Haining; Liu, Xiaochun
Abstract: In this paper, we study the existence of multiple positive and negative solutions for a class of Kirchhoff type problems on an unbounded domain. Using the variational methods, we show that our problem admits at least two positive and two negative solutions under different conditions. A cut-off functional is utilized to obtain the bounded Palais–Smale sequences.